Pemberdayaan Masyarakat melalui Pelatihan “Ecoprint Tote Bag” Bermotif Daun sebagai Implementasi Gerakan Manajemen Lingkungan Organik - Hayati, Rahmah; Mulyadi , Mulyadi; Lola , Lola; Bambangta, Bambangta; Gayola S, Anggi (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to increase the creativity and productivity of the people of Piyeung Datu Village, Montasik District, Aceh Besar Regency through training in making tote bags using ecoprint techniques based on the use of local leaves. The community service program was implemented by lecturers and students of KKN Abulyatama University by providing counseling, demonstrations, and direct assistance to the people of Piyeung Datu Village. The implementation method included material presentation, ecoprinting practice, and ongoing technical guidance. The results of the activity showed an increase in the skills of participants in producing tote bags with unique and valuable local plant leaf motifs, which were then given the product identity "Topida (Piyeung Datu Tote Bag)". This activity not only encourages community creativity, but also opens up opportunities for the formation of ecoprint-based business units with product diversification. Thus, this PKM program has the potential to support local economic empowerment and improve the welfare of the people of Piyeung Datu Village in a sustainable manner.